Perkembangan Peradaban Islam Fase Madinah - Nabila Salsabila; Dea Safitri; Mutiara Hilda; Rizka Julia Putri (Journal on Education, 2023)
The purpose of this research is to find out the development of Islamic civilization in the Medina phase. Here we can see the accuracy of the Prophet in taking coaching steps, because only with the support of the ummah can uphold the society that will be built. And the unity of the ummah can only be realized if there is brotherhood and mutual love, this is important for the Messenger of Allah to do because remnants of ignorance and tribal fanaticism may still arise if not immediately brotherhood between the Muhajirin and Ansar and fellow Ansar people, previously there were frequent wars between they. On the other hand, it aims to foster mutual help, where the Muhajirin come to Medina without bringing anything. With a solid Islamic society based on solid monotheism and unity that loves one another, agreements with outsiders can be made. This research uses the method (library research) by collecting a number of books, magazines, journals, lifet which are related to the problem and research objectives. Data collection with the results of previous research which supports data on research themes related to the development of the Islamic civilization of the Medina phase with the research process starting with the stages of identifying, finding relevant information, analyzing the findings, and then developing and expressing them into new findings related to the development of the Islamic civilization phase medina.